Relationship between Public Service Motivation, Job Satisfaction, Organizational Commitment, and Public Service-Oriented Behavior : The Cases of Local Administrative Organization Executives in Maha Sarakham, Roi Et, and Kalasin Provinces - Watthanakul, Preeyanuch (Journal for Developing the Social and Community, 2018)
This study aims to determine the level of motivation in public service, satisfaction level of performance, the organizational commitment and the level of interest in the delivery of public services. Also, study the influence of motivation in public services on the influence of motivation in public services to the satisfaction of the operation, organizational commitment and attention to the delivery of public services. The sample in this study, including 201 sample executives from local governments in Maha Sarakham, Roi Et, and Kalasin were selected by stratified random sampling method and Sampling Simple. The results from the level of motivation in public service found that for executives from local governments from Maha Sarakham, Roi Et, and Kalasin are high. If considered as a province, executives from Roi Et local governments (mean = 4.47) has a higher average in the level of motivation in public service than executives from Maha Sarakham local governments (mean = 4.38) and from Kalasin (mean = 4.32), respectively. The results from the measurement of organizational commitment indicate that the level of organizational commitment for executives from all three local governments are at high level, considered as a province, executives from Roi Et local governments (mean = 4.10) has a higher average in the organizational commitment than executives from Maha Sarakham local governments (mean = 4.03) and from Kalasin (mean = 4.03), respectively. The results from the level of interest in the delivery of public services indicate that the level of interest in the delivery of public services for executives from all three local governments is at high level. If considered as a province, executives from Kalasin local governments (mean = 4.31) has a higher average than executives from Roi Et (mean = 4.30) and from Maha Sarakham (mean = 4.26), respectively. The results of the analysis of variance (One-Way ANOVA) found that no significant difference in the statistical in the motivation levels in the public service, satisfaction level of performance, the organizational commitment and the level of interest in the delivery of public services in all three provinces. However, multiple regression analysis results suggest that the motivation in the public service can predict satisfaction level of performance, organizational commitment and the level of interest in the delivery of public services. Finally, researcher have other suggestion includes suggestions to promote motivation levels in the public service among the executive of the local governments by using the social construct theory or applications of the theory that by relying on social sectors, such as the role of the public sector, mass media, or local government to join the influential leadership roles, especially the expectations of moral action of the local government. This behavior is one of the main elements of motivation in the public service, in order to know the level of motivation in their public service to guide planning, promotion, motivation levels in the public service properly.